Numerical and experimental study with optimization of a small–scale vertical axis wind turbine - Arsalan, Omar Farooq Izzat (My University, 2017)
In the current study, a small-scale wind turbine is investigated in order to provide energy requirements such as lighting in urban areas and small scale power needs. Regarding the application, a small- scale wind turbine has been analyzed aerodynamically and in terms of feasibility aspects. The turbine is designed to be a starting-up type which needs no initial excitation even at lower wind speeds. A three blade vertical axes savonius type has been considered in this study. Analytical and numerical analyses in two-dimensions are carried out to determine the optimum design and the most efficient blade geometry. The geometry and position of stators have been modeled to improve the structure of turbine and position of stators which increase the efficiency due to diffuser angle to guide wind through the blades. Numerical studies are conducted in 3 dimensional CFD which shows that the peak efficiency of the turbine has been improved up to 35%. The selected geometry which is determined to be elliptical shaped with circular end profile has higher efficiency than the circular shaped geometry. The optimum geometry has been built to carry out the related measurements. Model assessment has been carried out by comparing the experimental data and measured power with the simulation outputs. Keywords: Renewable energy, wind energy, vertical axis Wind Turbine, savonius rotor.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2017
Keywords: Renewable energy; Wind energy; Savonius rotor